Integracion economica en el Caribe. - Samuel, Wendell A. (1990)
Claims that market integration will not lead to an integration of production in the region because the structure of production is very weak. Contends that production should be integrated first, and recommends cooperation between small and medium sized enterprises in the different countries as a means of moving towards a coordinated production that will make market integration possible.